Qui sont les sémioticiens et que font-ils ? Enquête sur leurs relations avec le design et des médias - Bernard Darras (Signata, 2012)
Who are the semioticians who are working at the university or in agencies and corporations and sometimes in both worlds? This survey gathers, exposes and interprets the answers from 206 European and American semioticians talking about the definition of their discipline and of their activities.The analyse of the responses gives the picture of a vibrant community, interconnected and cooperative whose theoretical choices are divided between the pragmatic, cognitive and cultural semiotics, and the different variants of semiotics coming from the structuralism, but also a wide variety of syncretism.The survey focuses particularly on relations that semiotics and the semioticians have with the various forms of design and media. These relationships constitute a rich, diverse and productive panorama concerned by the entire chain of production and reception of the products of design and media.